isoSTED nanoscopy with intrinsic beam alignment - Curdt, Franziska; Herr, Simon J.; Lutz, Tobias; Schmidt, Roman; Engelhardt, Johann; Sahl, Steffen Joachim; Hell, Stefan (Optics express, 2015)
Despite the need for isotropic optical resolution in a growing number of applications, the majority of super-resolution fluorescence microscopy setups still do not attain an axial resolution comparable to that in the lateral dimensions. Three-dimensional (3D) nanoscopy implementations that employ only a single objective lens typically feature a trade-off between axial and lateral resolution. 4Pi arrangements, in which the sample is illuminated coherently through two opposing lenses, have proven their potential for rendering the resolution isotropic. However, instrument complexity due to a large number of alignment parameters has so far thwarted the dissemination of this approach. Here, we present a 4Pi-STED setup combination, also called isoSTED nanoscope, where the STED and excitation beams are intrinsically co-aligned. A highly robust and convenient 4Pi cavity allows easy handling without the need for readjustments during imaging experiments.